Dataset for supporting a modular autoinduction device for control of gene expression in Bacillus subtilis - Correa, Graciely Gomes [UNESP] (2020)
Modular and tuneable genetic tools for Metabolic Engineering fuels the development of chassis for the efficient production of biocompounds at industrial scale. We have constructed an autoinduction device for gene expression in Bacillus subtilis based on the LuxR/I quorum sensing system [1]. Here, we present raw and processed data regarding to B. subtilis growth measured as OD600, performed in three different scales: microcultivation on 96-well plates (200 µL), test tubes (12 mL), and Erlenmeyer flasks (50 mL). We also present raw and processed data on gene expression measured as GFP fluorescence (485/535 nm), luminescence and riboflavin production. Measurements were performed on a microplate reader Tecan 200 PRO (iControl software) and on spectrophotometer (Thermo Fisher Scientific GENESYS 10S UV-Vis). Processed data are presented as product/OD600, maximum and minimum promoter activity, fold of induction, and the induction OD600.